Performance-enhanced biosensors constructed using one-dimensional nanostructured materials - Zang, Jianfeng (2009)
One-dimensional (1D) nanostructured materials possess unique electronic, optical and mechanical properties owing to their nanoscale dimension and high aspect ratio nature. At nanoscale, the direct interaction between the size-comparable transducer elements and the individual target biomolecules produces great opportunities for the construction of performance-enhanced biosensors. Although various nanomaterials-based biosensors have been developed, it remains a great challenge to synthesize 1D nanostructured materials with specific properties and to tailor the 1D nanostructure-based biosensors for multiple detections with rapid response, high sensitivity, and good stability. Therefore, two main objectives were set in this thesis: (1) to synthesize 1D nanostructures of conductive polymers (CPs) with special properties; (2) to construct high performance biosensors by employing 1D nanostructured materials and building novel architectures through nanoengineering approaches. To fulfil the goals, several strategies were employed in this study: (1) to electrochemically synthesize 1D nanostructured CPs with novel chemical and physical properties by developing a template-free synthetic approach, construct biosensors by using the synthesized 1D nanostructured CPs, and further apply the constructed sensors to detect glucose; (2) to investigate the mechanism of the formation of 1D nanostructured CPs; (3) to enhance the performance of 1D nanostructure-based biosensors by developing novel nanoengineering approaches; and (4) to design and fabricate economic arrayed biosensor chips for the multiple detections of lactate and glucose.